Technology Acceptance Model in the Analysis of the Influence Of E-Learning Implementation to Students' Motivation - Asiyah, Siti; Budiyanto, Cucuk W; Tamrin, A G (IJIE (Indonesian Journal of Informatics Education), 2018)
One effort to improve the quality of education is the innovation of learning, one of them with the application of e-learning. With the help of the TAM tool as an analysis in measuring the acceptance attitude of teachers and students. Seeing from the side of ease of use and e-learning use. The purpose of this research is to 1) to know the acceptance of students to an information system applied in the form of e-learning, and 2) to analyze the effect of e-learning implementation on learning motivation of learners. More specifically, the study will evaluate the application of LMS Edmodo and Schoology. The analysis used is descriptive statistical analysis for the disseminated questionnaire and thematic analysis for the interview data obtained. The result of this research is the use of e-learning better if collaborated with conventional learning. So that will complement each deficiency of both e-learning and conventional learning.